The Fifth-Century AD Riverine Barge of Santa Maria in Padovetere (Ferrara, Italy): A Multidisciplinary Approach to its Environment and Shipbuilding Techniques. (2nd January 2021) - Beltrame, C.; Mozzi, P.; Forti, A.; Maritan, M.; Rucco, A. A.; Vavasori, A.; Miola, A.
ABSTRACT: This paper presents the results of a multidisciplinary investigation of the wreck of a riverine flat-bottom sewn barge dated to the fifth century AD. The wreck was recovered west of the city of Comacchio (Ferrara, North Italy), near the sixth century church Santa Maria in Padovetere (SMP). It was found in the silty sediments filling a paleo channel of the Po River and is one of the very few well-preserved inland watercrafts from the Roman period known in southern Europe. Thanks to the high level of conservation of the organic matter, archaeobotanical analyses of the bilge sediments, rope fragments, caulking, and wood elements and chemical analyses of the pitch have revealed the local provenance of the barge's materials, the craft's possible use, and the environment in which it sailed. A geomorphological study of the area where the wreck was found led to a reconstruction of the flooding event that could be responsible for the barge's abandonment.